(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Diasporic literature, which draws on the social implications of the diaspora, is a thriving subgenre of postmodernism. The study questions the truth of generalized beliefs and pushes back against efforts to create meta narratives that claim to represent the diasporic mind. In the latter sections of the article, we briefly discuss the creative imprint of the diasporic realm of life as shown in diasporic literature. Research into diasporic and feminine studies is an essential and fascinating part of modern literary studies. The history of diasporic literature begins with the emigration of the poor to more prosperous countries like the United States, Britain, Canada, Trinidad, etc. Migration is a common result of a country’s colonial past. The purpose of this article is to examine Bharati Mukherjee’s and Jhumpa Lahiri’s depiction of immigrants, focusing on their profound sense of isolation in the current circumstances, their longing for the past, and the difficulties of bridging the two cultures via their sense of identity.